2020
DOI: 10.1109/access.2020.3006423
|View full text |Cite
|
Sign up to set email alerts
|

Marker-Less Monitoring Protocol to Analyze Biomechanical Joint Metrics During Pedaling

Abstract: Marker-less systems are becoming popular to detect a human skeleton in an image automatically. However, these systems have difficulties in tracking points when part of the body is hidden, or there is an artifact that does not belong to the subject (e.g., a bicycle). We present a low-cost tracking system combined with economic force-measurement sensors that allows the calculation of individual joint moments and powers affordable for anybody. The system integrates OpenPose (deep-learning based C++ library to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, self-occlusion errors are a major issue, often causing joint center locations to be missing for one or more frames and contribute to instances where the opposite limb is incorrectly detected ( e.g. , right knee labelled as the left knee) ( Serrancolí et al, 2020 ; Stenum, Rossi & Roemmich, 2021 ). Similar to marker-based methods, obtaining biomechanically relevant 2D planar joint angles requires an assumption that the camera is perfectly aligned with frontal or sagittal plane movements ( Stenum, Rossi & Roemmich, 2021 ).…”
Section: Performance Of Current Markerless Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, self-occlusion errors are a major issue, often causing joint center locations to be missing for one or more frames and contribute to instances where the opposite limb is incorrectly detected ( e.g. , right knee labelled as the left knee) ( Serrancolí et al, 2020 ; Stenum, Rossi & Roemmich, 2021 ). Similar to marker-based methods, obtaining biomechanically relevant 2D planar joint angles requires an assumption that the camera is perfectly aligned with frontal or sagittal plane movements ( Stenum, Rossi & Roemmich, 2021 ).…”
Section: Performance Of Current Markerless Applicationsmentioning
confidence: 99%
“…While not strictly monocular, Serrancolí et al (2020) and Stenum, Rossi & Roemmich (2021) used two video cameras (25–60 Hz), placed on either side of a person, to extract information of the side closest to each camera and negate occlusion errors during walking over-ground or cycling on an ergometer. During walking, temporal differences were on average within 1 frame and spatial differences were less than one cm, although maximum differences were as high as 20 cm ( Stenum, Rossi & Roemmich, 2021 ).…”
Section: Performance Of Current Markerless Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both works trained their own model with DeepLabCut. Serrancoli et al [ 30 ] fused OpenPose and force sensors to retrieve joint dynamics in a pedaling task.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, whenever markers are properly attached to bony landmarks they are considered a gold standard method. The use of marker-less methods to extract joint centres from video has been attempted in several studies (Grigg et al, 2018;Needham et al, 2017;Ong et al, 2017;Serrancolí et al, 2020). Ong et al (2017) observed differences of <1° for various joint angles using a marker-less tracking system during walking and jogging, demonstrating promising outcomes.…”
mentioning
confidence: 99%